CTWR: Coffee Talk With Rozie: at the forefront of internalising the global goals / Roziah Janor - Janor, Roziah (UiTM Press, 2023)
This book contains 12 chapters which correspond to the 12 CTWR episodes that were aired monthly in 2022. Each episode touches on a specific issue related to sustainability that is guided by the SDGs and serves as a complement, and not a replacement, to the actual episodes that were aired. While the contents of each chapter does discuss the SDG goals in relation to how it is addressed in UiTM, it is not a comprehensive discussion of the activities and initiatives that are currently being done. Rather, it is my hope that this book will serve as a good introduction to the SDGs and how UiTM champions sustainability in its numerous activities. I believe that we should begin to talk about and continuously discuss these issues as part of our responsibility to shape a better future for our university and nation tomorrow.